De volta para casa: a distribuição dos brasileiros retornados do exterior - Wilson Fusco; Sylvain Souchaud (Confins)
In South America, the study of return migration has been little considered because, at first, the migration flows, from Europe, Asia and Africa, were regarded in one direction only. The progress of the systematic approach has given importance to the theme of return. Nevertheless, the return of migrants is included in the modalities of the transfers and impacts on the places of origin. On the other hand, a specific category of return, known as "ethnic", has been developed. In this case, migration involves a historical process that, across the generations, will feed a national political project, and even a nationalist one. Around the historical experience of remoteness, we build a collective identity, crystallized around the return. In this paper, we consider the return depending on the actual characteristics of emigration flows from which it originates. Starting from three case studies, the return from Japan, Paraguay and the United States, we insist in the first case, on the importance of training and consolidation of historical flow outward in the return's organization. In case of return from Paraguay, we stress the importance of the local context in Brazil, where the dynamics of the agricultural frontier activate flows and counter-flows. The return from the United States, in turn, "has no history", but is structured through strong social ties, that underlie the initial migration from Brazil